Penerapan Metode Naïve Bayes Dalam Memprediksi Kepuasan Mahasiswa Terhadap Cara Pengajaran Dosen - Putri Ramadani; Gunadi Widi Nurcahyo; Billy Hendrik (LPPM STIKOM Tunas Bangsa, 2024)
Student satisfaction in higher education is the main focus in improving the quality of education. In the Tridharma paradigm, satisfaction is measured through a comparison of expectations and teaching realization as the main indicator of learning effectiveness. This research method uses Naïve Bayes classification, through the steps of reading training data, calculating prior probabilities, training data probabilities for each category, reading testing data, and calculating final probabilities. This research aims to evaluate student satisfaction with lecturers' teaching at the LP3I Polytechnic, Padang Campus. The data used in this research was 574. The results of research with 574 data (516 training and 58 testing) showed that 52 data (89.648%) stated